HUBUNGAN POWER OTOT TUNGKAI DENGAN HASIL LOMPAT TINGGI GAYA STRADDLE PADA MAHASISWA PUTRA KELAS B PENJASKESREK ANGKATAN 2013 UNIVERSITAS RIAU - Damayanti, Fitry; ', Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This research was conducted to determine whether there is a correlation limb muscle power with the result of the high jump at the straddle style class B male students Penjaskesrek 2013 Riau University, so that at the time of the straddle-style high jump with a leap to do the maximum. Forms of this research is a correlation study, the population in this study were male students class B Penjaskesrek 2013 University of Riau, the sample in this study all students B Penjaskesrek son generation 2013 Riau University, totaling 26 people. A sampling technique that the overall population (total sampling). The instruments used in this research is the leg muscle power tests, to measure muscle power and high jump leg straddle style for measuring the height of the jump. After that, the data is processed with statistical, normality test with lilifors test at significant level 0,05α. The hypothesis is suspected there is a significant relationship between limb muscle power with the result of the high jump at the straddle style class B male students Penjaskesrek force in 2013 University of Riau. Based on analysis of test lilifors produce Lhitung (x) of 0,1618dan Ltabel0,173, Lhitung (y) of 0.1724 and 0,173 Ltabel means Lhitung <Ltabel, then the samples come from normal populations berdristribusi. Then from the calculation of product moment correlation between limb muscle power with a crescent kick velocity obtained rhitung 0.7663 and 0.396 rtabel means rhitung> rtabel consequently Ha Ho accepted and rejected. The results showed that there is a significant relationship between limb muscle power with the result of the high jump at the straddle style class B male students Penjaskesrek 2013 Riau University.Keywords: leg muscle power, the result of high jump style sraddle